PENGARUH FINANCIAL DISTRESS, REAL EARNINGS MANAGEMENT DAN CORPORATE GOVERNANCE TERHADAP TAX AGGRESSIVENESS - Sholehudin Adi Nugroho; Amrie Firmansyah (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
This study is aimed to examine the effect of financial distress, real earnings management, and corporate governanceon tax aggressiveness. Using samples from manufacturing companies listed on the Indonesia Stock Exchange in the period 2011 to 2015, the data will be examined with fixed effect approach method. The results of this study indicate that financial distress does not affect on tax aggressiveness. While from real earnings management variables, only through manipulation of sales as which affects positive significantly on tax aggressiveness. On the contrary, manipulation of the production and manipulation of discretionary expenses precisely give the opposite effect. In addition, corporate governance consists of the audit committee and the percentage of institutional ownership can reduce tax aggressiveness, meanwhile the third measure (the percentage of independent commissioners) shows the opposite result..